TIMBER STRUCTURAL TECHNIQUES FROM THE DAWN OF THE CIVILIZATION TO THE EXPANSION OF CITIES IN THE XIX CENTURY IN EUROPE AND ITS COLONIES (2019)
This paper is a general description of the state-of-the-art on the European and colonial building techniques found in wooden buildings that currently exist. The description of the use and diffusion of the wooden structures is made by a brief explanation of the relative structural systems, as well as the peculiarities of the elements that compose it, its operating principles, the points of weakness and the joints used. Thus, the English and German techniques of structural timber frameworks are described in detail. On the other hand, other structural techniques and their evolution are presented through a review of works and documents that describe them accurately.